Measuring Government Performance in CPNS Recruitment: Between Hope and Reality - Hikmah Muhaimin; Alfiana Dwi Astuti; Marta Sari Dwi Ayuningtyas; Ion Sastra Piawai Aziz (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
Recruitment of Civil Servant Candidates (CPNS) is an important element in creating an effective and professional bureaucracy. However, this process still faces various challenges such as lack of transparency, mismatch of formation with agency needs, and nepotism and corruption practices. This study uses a qualitative descriptive analysis method to evaluate government performance in organizing CPNS recruitment, focusing on administrative barriers, regulations, and organizational culture. The results of the study indicate that technology-based systems such as the Computer Assisted Test (CAT) have increased the transparency of the initial selection, but further stages such as interviews and document verification are still prone to intervention. In addition, disparities in access to education and technology in disadvantaged areas hinder the inclusiveness of the recruitment process. Recommendations include strengthening the competency-based selection system, increasing supervision, and affirmative policies for applicants from remote areas. With comprehensive improvements, the CPNS recruitment system can become the foundation for a responsive and service-oriented bureaucracy.